2017
DOI: 10.1371/journal.pone.0185065
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-1 modulates TGFβ signaling to drive glioblastoma growth and recurrence after anti-angiogenic therapy

Abstract: Glioblastoma (GBM) is a rapidly progressive brain cancer that exploits the neural microenvironment, and particularly blood vessels, for selective growth and survival. Anti-angiogenic agents such as the vascular endothelial growth factor-A (VEGF-A) blocking antibody bevacizumab yield short-term benefits to patients due to blood vessel regression and stabilization of vascular permeability. However, tumor recurrence is common, and this is associated with acquired resistance to bevacizumab. The mechanisms that dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 52 publications
1
40
0
Order By: Relevance
“…In tumor cells, NRP1 expression is upregulated along with GBM tumor progression. Additionally, NRP1 can bind with TGFβRII to activate Smad3 signaling to drive GBM development and the TGF-β/Smad3 signaling is NRP1-dependent during the process (16). In the central nervous system, NRP1 can balance integrin β8-activated TGF-β signaling to control sprouting angiogenesis (42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In tumor cells, NRP1 expression is upregulated along with GBM tumor progression. Additionally, NRP1 can bind with TGFβRII to activate Smad3 signaling to drive GBM development and the TGF-β/Smad3 signaling is NRP1-dependent during the process (16). In the central nervous system, NRP1 can balance integrin β8-activated TGF-β signaling to control sprouting angiogenesis (42).…”
Section: Discussionmentioning
confidence: 99%
“…3C). Previous studies have reported that NRP1, as a co-receptor of TGF-β1, can modulate the TGF-β signaling pathway in various cell types (16,21). In addition, from the public database LinkedOmics (http://www.linkedomics.…”
Section: High Expression Of Nrp1 Promotes Nsclc Metastasis In Vivo Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have shown the contribution of different molecules in conferring drug resistance. The transmembrane receptor, neuropilin‐1 (NRP‐1) mediates angiogenesis through VEGF‐A and enhances TGF‐β1 signalling via Smad and hence promotes resistance to anti‐angiogenic agents (Kwiatkowski et al, ). Previously, we reported a significant increase in NRP‐1 levels in the basal subtype of breast cancer, compared with other subtypes (Naik et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Kwiatkowski and his colleagues showed that NRP1 acts as a co-receptor with TGFβR2 to enhance TGF-β1 receptor signaling via Smad3 in Glioblastoma [16]. Thus, the relationship between NRP1 and TGF-β signaling pathways in NSCLC requires to be verified.…”
Section: Introductionmentioning
confidence: 99%